Combined resistance and aerobic training improves lung function and mechanics and fibrotic biomarkers in overweight and obese women - Silva-Reis, Anamei; Rodrigues Brandao-Rangel, Maysa Alves; Moraes-Ferreira, Renilson; Gonçalves-Alves, Thiago Gibson; Souza-Palmeira, Victor Hugo; Aquino-Santos, Helida Cristina; Bachi, Andre Luis Lacerda; Oliveira, Luis Vicente Franco de; Lopes-Martins, Rodrigo Álvaro Brandão; Oliveira-Silva, Iranse; Albertini, Regiane; Frison, Claudio Ricardo; et al. (Frontiers in Physiology, 2022)
Background: Obesity impairs lung function and mechanics and leads to low-grade inflammation, but the effects of combined physical exercise (CPE) on that are unknown. Methods: We investigated the effects of 12 weeks of combined physical exercise (aerobic + resistance training), in non-obese (n = 12), overweight (n = 17), and obese grade I (n = 11) women. Lung function and lung mechanics were evaluated. The systemic immune response was evaluated by whole blood analysis and biomarker measurements, while pulmonary fibrotic biomarkers were evaluated in the breath condensate. Result: CPE improved forced vital capacity (FVC) % (p < 0.001) and peak expiratory flow (PEF) % (p < 0.0003) in the obese group; resistance of the respiratory system (R5Hz) in non-obese (p < 0.0099), overweight (p < 0.0005), and obese (p < 0.0001) groups; resistance of proximal airways (R20Hz) in non-obese (p < 0.01), overweight (p < 0.0009), and obese (p < 0.0001) groups; resistance of distal airways (R5Hz–R20Hz) in non-obese (p < 0.01), overweight (p < 0.0012), and obese (p < 0.0001) groups; reactance of the respiratory system (X5Hz) in non-obese (p < 0.01), overweight (p < 0.0006), and obese (p < 0.0005) groups; impedance of the respiratory system (Z5Hz) in non-obese (p < 0.0099), overweight (p < 0.0005), and obese (p < 0.0001) groups; central resistance (RCentral) in non-obese (p < 0.01), overweight (p < 0.001), and obese (p < 0.0003) groups; and the peripheral resistance (RPeripheral) in non-obese (p < 0.03), overweight (p < 0.001), and obese (p < 0.0002) groups. CPE reduced the pro-fibrotic IGF-1 levels in BC in overweight (p < 0.0094) and obese groups (p < 0.0001) and increased anti-fibrotic Klotho levels in BC in obese (p < 0.0001) groups, and reduced levels of exhaled nitric oxide in overweight (p < 0.03) and obese (p < 0.0001) groups. Conclusion: CPE improves lung function, mechanics, and pulmonary immune response in overweight and obese grade I women by increasing anti-fibrotic protein Klotho and reducing pro-fibrotic IGF-1.